Emergence of common lambsquarters (Chenopodium album L.) is influenced by the landscape position in which seeds developed. Issue 1 (27th February 2020) - Papiernik, Sharon K.; Forcella, Frank; Amundson, Gary B.
Abstract: In a 2‐yr field study, we evaluated the emergence and early growth of Chenopodium album L. (common lambsquarters) seedlings as affected by the landscape position in which the seeds (i) developed, (ii) overwintered, and (iii) were planted. Results indicated that a higher proportion of seeds originating from lower slope positions emerged compared with seeds originating from the backslope or upper slope. The timing of emergence was the same for all seed source locations. There was no influence of overwintering location on weed emergence. Regardless of the seed source, we observed faster emergence and growth of C. album planted in the lower slope, where soil conditions were more conducive to growth. These experiments will support the development of new strategies and decision aids to improve weed management.